The Influence of Green Marketing Mix, Brand Image, and Buying Motivation on Buying Interest in Cosmetics Products - Tika Firayanti; Audita Nuvriasari (LifeSciFi, 2025)
Indonesia's cosmetic industry is growing rapidly, shown by the wide variety of products from both local and international brands. This study aims to analyze the influence of the Green Marketing Mix, Brand Image, and Purchase Motivation on consumer interest in eco-friendly cosmetic products. A quantitative method was used with 100 respondents selected through non-probability sampling. The results showed that the Green Marketing Mix did not have a positive and significant impact on consumer purchase interest. On the other hand, Brand Image had a positive and significant influence, meaning that consumers' positive perception of a brand plays an important role in increasing their interest in eco-friendly products. Meanwhile, Purchase Motivation also did not show a positive and significant effect on consumer interest. These findings suggest that in the Indonesian cosmetic market, a strong brand image is more effective in attracting consumer interest in green products than green marketing strategies or individual motivations to buy.